Genomic analyses reveal FAM84B and the NOTCH pathway are associated with the progression of esophageal squamous cell carcinoma. Issue 1 (11th January 2016) - Cheng, Caixia; Cui, Heyang; Zhang, Ling; Jia, Zhiwu; Song, Bin; Wang, Fang; Li, Yaoping; Liu, Jing; Kong, Pengzhou; Shi, Ruyi; Bi, Yanghui; Yang, Bin; et al.
Abstract: Background: Esophageal squamous cell carcinoma (ESCC) is the sixth most lethal cancer worldwide and the fourth most lethal cancer in China. Genomic characterization of tumors, particularly those of different stages, is likely to reveal additional oncogenic mechanisms. Although copy number alterations and somatic point mutations associated with the development of ESCC have been identified by array-based technologies and genome-wide studies, the genomic characterization of ESCCs from different stages of the disease has not been explored. Here, we have performed either whole-genome sequencing or whole-exome sequencing on 51 stage I and 53 stage III ESCC patients to characterize the genomic alterations that occur during the various clinical stages of ESCC, and further validated these changes in 36 atypical hyperplasia samples. Results: Recurrent somatic amplifications at 8q were found to be enriched in stage I tumors and the deletions of 4p-q and 5q were particularly identified in stage III tumors. In particular, the FAM84B gene was amplified and overexpressed in preclinical and ESCC tumors. Knockdown of FAM84B in ESCC cell lines significantly reduced in vitro cell growth, migration and invasion. Although the cancer-associated genes TP53, PIK3CA, CDKN2A and their pathways showed no significant difference between stage I and stage III tumors, we identified and validated a prevalence of mutations in NOTCH1 and in the NOTCH pathway that indicate that they are involved in the preclinical and early stages of ESCC. Conclusions: Our results suggest that FAM84B and the NOTCH pathway are involved in the progression of ESCC and may be potential diagnostic targets for ESCC susceptibility.